The spatial dimension of trade- and FDI-driven productivity growth in Chinese provinces: A global cointegration approach - Timo Mitze; Selin Özyurt (European Regional Science Association (ERSA), 2012)
Since the introduction of its "open door" policy in the late 1970s, China has been attracting a growing share of FDI inflows and its international trade integration has advanced considerably. In this study, we take a closer look at the regional growth impact of the Chinese internationalization activity on labour productivity over the period 1979-2006. Our empirical analysis thereby extends the existing empirical literature by considering the likely spatial effects associated with Trade- and FDI-led growth in a dynamic error correction modelling framework. Our results indicate that, in the long-run relationship, regional labour productivity is indeed driven by direct and indirect spatial effects if FDI and trade activity next to further supply side factors such as the regional infrastructure equipment and human capital endowment. Similarly, in the short-run, changes in FDI activity and especially human capital variables are found to matter for the regional growth dynamics.
Keywords: 330